ADAR2 enzymes: efficient site-specific RNA editors with gene therapy aspirations - Hajji, Khadija; Sedmík, Jiří; Cherian, Anna; Amoruso, Damiano; Keegan, Liam P; O'Connell, Mary A (RNA (New York, N.Y.), 2022)
The adenosine deaminase acting on RNA (ADAR) enzymes are essential for neuronal function and innate immune control. ADAR1 RNA editing prevents aberrant activation of antiviral dsRNA sensors through editing of long, double-stranded RNAs (dsRNAs). In this review, we focus on the ADAR2 proteins involved in the efficient, highly site-specific RNA editing to recode open reading frames first discovered in the GRIA2 transcript encoding the key GLUA2 subunit of AMPA receptors; ADAR1 proteins also edit many of these sites. We summarize the history of ADAR2 protein research and give an up-to-date review of ADAR2 structural studies, human ADARBI (ADAR2) mutants causing severe infant seizures, and mouse disease models. Structural studies on ADARs and their RNA substrates facilitate current efforts to develop ADAR RNA editing gene therapy to edit disease-causing single nucleotide polymorphisms (SNPs). Artificial ADAR guide RNAs are being developed to retarget ADAR RNA editing to new target transcripts in order to correct SNP mutations in them at the RNA level. Site-specific RNA editing has been expanded to recode hundreds of sites in CNS transcripts in Drosophila and cephalopods. In Drosophila and C. elegans, ADAR RNA editing also suppresses responses to self dsRNA.
Keywords: Animals; Antiviral Agents; genetická terapie; ADAR; ADARB1; recoding RNA editing; RNA, Double-Stranded; antivirové látky; Caenorhabditis elegans; dvouvláknová RNA; Drosophila; proteiny vázající RNA; lidé; Mice; Receptors, AMPA; myši; adenosindeaminasa; AMPA receptory; dsRNA; RNA-Binding Proteins; Genetic Therapy; neurons; zvířata; Adenosine Deaminase; Humans